Aplikasi Isotop Alam (18O, 2H dan 14C) untuk Studi Dinamika Air Tanah dan Hubungannya dengan Air Sungai di Daerah Bandung - Pujiindiyati, Evarista Ristin; Satrio, Satrio (BRIN Publishing, 2013)
Water table in the center of Bandung basin has been decreased around 1-2 m/year since 1990 whereas in the slope has been decreased at higher level of 15 m. Water level decreasing are going to increase continuously because of increasing number of deep wells (>40 m). In 1970, there were 96 deep wells which have been registered, but now number of deep wells is estimated of more than 4700. Therefore, a study of interrelationship between groundwater and surface water, and determination of recharge area for Bandung basin are crucial research to be conducted. Stable isotopes in nature such as 2H and 18O, and radioactive isotope of 14C can give important information about groundwater dynamic pattern. In this research, 24 deep groundwater samples, 28 shallow groundwater and river water samples (Citarum, Cikapundung, Cikeruh and Citarik rivers) and shallow groundwater along the rivers were collected. Results from plotting d18O and d2H showed that most of shallow groundwater did not relate to river water except three locations, they are Loteng Sumbersari and Bojong Mas groundwater near to Citarum river, and groundwater near to Cikapundung river. Isotope 14C analysis indicated that deep groundwater of Bandung basin did not show relationship either by shallow groundwater or river water. Its iso-age line contour determined that dynamic pattern of deep groundwater in Bandung basin comes from northern and southern hills to direction of north-west area such that both areas are suggested as conservation zone. Rate of deep groundwater movement predicted from iso-age contour is around 0.25 to 3 m/year.